Syntagma in pronunciation training – prosodic units vs. syntactic phrases - Żytyńska, Małgorzata (Acta Universitatis Lodziensis. Folia Germanica, 2023)
The article deals with the prosodic competence of learners of German, and more precisely with prosodic units. It is not always easy for learners to correctly determine these units and consequently to set correct sentence accents. Lack of correspondence between prosodic and syntactic units leads sometimes to prosodic errors. The article tries to analyze these discrepancies between prosodic units and syntactic phrases in order to determine certain regularities.